Effect of MXene fillers on the electrical conductivity of Ag-coated Cu conductive adhesives. Issue 6 (15th March 2023) - Lu, WenBin; Zhang, Yan; Zhou, JianPing; Sun, DaQian; Li, HongMei
Abstract: The conductive adhesives were made using Ag-coated Cu and V2 CTx  + Ag + MWCNTs + Ag composites as fillers. The effects of V2 CTx  + Ag + MWCNTs + Ag composites content on the conductivity and microstructural properties of the conductive adhesives were investigated using two-point resistance measurements, scanning electron microscopy and XRD, respectively. The results showed that when the Ag package Cu content was 70%, the resistivity increased inversely with the V2 CTx  + Ag + MWCNTs + Ag (0.3%∼0.6%) content. Two-dimensional V2 CTx  + Ag + MWCNTs + Ag composites were obtained by solution mixing, offering the possibility to build up a large number of conductive networks. The synergistic effect of the Ag-claded Cu and V2 CTx  + Ag + MWCNTs + Ag composites significantly reduces the percolation threshold and conductivity of the conductive glue. In particular, the resistivity of the conductive glue is only 3.52 × 10 −6  Ω m at a content of 70% Ag-coated Cu and 0.3% V2 CTx  + Ag + MWCNTs + Ag composites. Inside the epoxy resin Ag-coated Cu is connected to each other to form a conductive pathway and V2 CTx  + Ag + MWCNTs + Ag composites is interspersed between the conductive pathways to form a conductive network for electron transport. The synergistic effect of the Ag-coated Cu and V2 CTx  + Ag + MWCNTs + Ag composites makes the epoxy resin conductive adhesive with good conductive properties.